Aircraft position estimation using angle of arrival of received radar signals - Freeha Majeed Amjad; Ahmad Zuri Sha'ameri; Kamaludin Mohamad Yusof; Paulson Eberechukwu (Bulletin of Electrical Engineering and Informatics, 2020)
With increasing demand of air traffic, there is a need to optimize the use of available airspace. Effective utilization of airspace relies on quality of aircraft surveillance. Active research is carried out for enhancements in surveillance techniques and various methods are evaluated for future use. This paper evaluates the use of multiple signal classification (MUSIC) based angle of arrival (AOA) estimation along with multiangulation for locating aircrafts from their electromagnetic wave emission. The performance evaluation of the system is presented by evaluating the AOA estimation errors and position estimation (PE) errors. The errors are evaluated by comparing the estimated value to the actual value. An analysis on the system parameters, AOA error and PE error are presented in the end. AOA errors are affected by the AOA value (emitter bearing), number of array elements, SNR and resolution of AOA estimation algorithm. Errors in AOA estimation lead to PE errors. The simulation results show small errors for short ranges. The system performance can be improved at the expense of computational time by using higher MUSIC resolution and larger antenna arrays